Composition for separator coating based on at least one fluoropolymer and at least one hydrophilic polymer

By using a polymer composition containing vinylidene fluoride and alkenyl ester, the problem that the lithium-ion battery separator coating is difficult to achieve good trade-offs in a number of properties is solved, and excellent dry and wet adhesion, ionic conductivity and thermal stability are achieved.

CN119894977APending Publication Date: 2025-04-25ARKEMA FRANCE SA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380064436.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-09
Filing Date
2023-09-08
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing lithium-ion battery separator coatings have difficulty achieving good trade-offs in terms of dry adhesion, wet adhesion, ion conductivity and thermal stability.

Method used

The appropriate crystallization temperature and performance characteristics are achieved by adjusting its mass ratio and structure using a composition comprising polymer P1 derived from vinylidene fluoride and a specific comonomer and polymer P2 derived from certain alkenyl esters.

Benefits of technology

The composition achieves a good trade-off between dry adhesion and wet adhesion, and maintains good ion conductivity and thermal stability, and is suitable for separator applications of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005301085420000151
    Figure BDA0005301085420000151
Patent Text Reader

Abstract

The present invention relates to a composition comprising a polymer P1 comprising monomeric units derived from vinylidene fluoride and optionally from a comonomer M1 compatible with vinylidene fluoride, and a polymer P2 comprising monomeric units derived from a monomer M2 of the formula R1R2C = C (R3) C (O) R wherein the substituents R1, R2 and R3 are independently selected from H and C1-C5 alkyl; r is selected from-NHC (CH3) 2CH2C (O) CH3 or-OR ', where R' is selected from H and C1-C18 alkyl optionally substituted by one or more-OH groups or a five or six membered heterocycle comprising at least one nitrogen atom in its ring chain, characterized in that the crystallization temperature of the composition is Tclt; -3.7496 x + 130, wherein x is the weight content of comonomer M1 relative to the total weight of polymer P1.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates generally to the field of electrical energy storage in Li-ion type rechargeable secondary batteries. More specifically, the present invention relates to compositions useful as separator coatings. Background Art

[0002] Lithium-ion batteries also include a separator arranged between the cathode and the anode. The separator must simultaneously have a low thickness, sufficient mechanical strength and temperature resistance, good electrochemical tolerance to the voltages to which they are exposed, an optimal affinity for the electrolyte, and more generally allow excellent ionic conductivity. Polyvinylidene fluoride (PVDF) and its derivatives are advantageous as polyolefin separator coatings because of their electrochemical stability and their high dielectric constant, which promotes ion dissociation and thus conductivity. US 2015 / 0155539 discloses separators based on PVDF copolymers, onto which side chains comprising hydrophilic units are grafted.

[0003] There is still a need to develop new coatings for separators which are easy to use and have a good compromise between dry adhesion, wet adhesion, ionic conductivity and thermal stability.

[0004] Accordingly, the present invention is directed to overcoming at least one of the disadvantages of the prior art. Summary of the invention

[0005] According to a first aspect, the present invention provides a composition comprising a polymer P1 comprising monomer units derived from vinylidene fluoride and optionally derived from a comonomer M1 compatible with vinylidene fluoride, and a polymer P2 comprising a monomer unit derived from a monomer of formula R 1 R 2 C=C(R 3 )C(O)R monomer M2 monomer unit, wherein the substituent R 1 , R 2 and R 3 R is selected from -NHC(CH3)2CH2C(O)CH3 or -OR', wherein R' is selected from H and C1-C5 alkyl, which is optionally substituted by one or more -OH groups or a five-membered or six-membered heterocyclic ring containing at least one nitrogen atom in its ring chain; 18 Alkyl, characterized in that the crystallization temperature of the composition is Tc<-3.7496x+130, wherein x is the mass content of the comonomer M1 based on the total weight of the polymer P1. The crystallization temperature is determined according to standard ASTM D3418.

[0006] The invention provides a composition which, when used to implement a separator composition, has a good compromise between different properties such as adhesion, conductivity and thermal stability. In particular, the production of a composition whose crystallization temperature complies with the above equation allows the desired properties to be achieved. In some cases, the composition may not have a crystallization temperature that can be measured by DSC according to standard ASTM D3418; these compositions are included in the composition according to the invention, since the crystallization temperature is considered to be zero. This type of composition can be obtained by a high mass content of comonomer M1 in the polymer P1, for example greater than 20% by weight, based on the total weight of the polymer P1.

[0007] According to a preferred embodiment, the mass ratio P1 / P2 ranges from 95 / 5 to 5 / 95, advantageously from 95 / 5 to 25 / 75, preferably from 95 / 5 to 40 / 60, in particular from 95 / 5 to 50 / 50.

[0008] According to a preferred embodiment, the polymer P1 is chosen from homopolymers of vinylidene fluoride and copolymers based on vinylidene fluoride and at least one comonomer M1 that is compatible with vinylidene fluoride.

[0009] According to a preferred embodiment, the at least one comonomer M1 compatible with vinylidene fluoride is selected from vinyl fluoride, tetrafluoroethylene, hexafluoropropylene, trifluoroethylene, chlorotrifluoroethylene, trifluoropropylene, tetrafluoropropylene, hexafluoroisobutylene, perfluorobutylethylene, pentafluoropropylene, perfluoroalkyl vinyl ether, bromotrifluoroethylene, chlorofluoroethylene, chlorotrifluoroethylene, chlorotrifluoropropylene and ethylene or a mixture thereof.

[0010] According to a preferred embodiment, the polymer P1 comprises: a monomer unit having at least one of the following functional groups, wherein the functional group is selected from carboxylic acid, carboxylic anhydride, carboxylic ester, epoxy, amide, hydroxyl, carbonyl, mercapto, sulfide, oxazoline, phenol, ester, ether, siloxane, sulfonic acid, sulfuric acid, phosphoric acid or phosphonic acid groups; preferably a monomer unit having at least one of the following functional groups, wherein the functional group is selected from carboxylic acid, carboxylic anhydride, carboxylic ester, hydroxyl, carbonyl and mercapto.

[0011] According to a preferred embodiment, the polymer P2 contains monomer units derived from monomers selected from the group consisting of methyl acrylate, ethyl acrylate, propyl acrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, n-dodecyl acrylate, amyl acrylate, isoamyl acrylate, hexyl acrylate, 2-ethylhexyl acrylate, diacetone acrylamide, lauryl acrylate, n-octyl acrylate, hydroxypropyl methacrylate, hydroxybutyl acrylate, hydroxyethyl methacrylate, hydroxyethyl acrylate, acrylic acid, methacrylic acid, methacrylic acid, methyl methacrylate, ethyl methacrylate, propyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, n-dodecyl methacrylate, amyl methacrylate, isoamyl methacrylate, hexyl methacrylate, 2-ethylhexyl methacrylate, lauryl methacrylate, n-octyl methacrylate, ureido methacrylate and mixtures thereof.

[0012] According to a preferred embodiment, the crystallization temperature of the composition is Tc<-3.7496x+128, wherein x is the mass content of the comonomer M1 based on the total weight of the polymer P1.

[0013] According to a preferred embodiment, the composition is in the form of a latex.

[0014] According to another aspect, the present invention provides a separator for an electrochemical device selected from: Li-ion, capacitor, double-layer capacitor and fuel cell membrane electrode assembly (MEA), the separator comprising a porous support and the composition according to the present invention.

[0015] According to a preferred embodiment, the composition has a mass ratio P1 / P2 ranging from 95 / 5 to 5 / 95.

[0016] According to another aspect, the present invention provides a Li-ion secondary battery comprising an anode, a cathode and a separator, wherein the separator is the separator according to the present invention. DETAILED DESCRIPTION

[0017] Composition

[0018] According to a first aspect of the present invention, a composition comprising a polymer P1 and a polymer P2 is provided. The polymer P1 is a fluorine-containing polymer, i.e., it comprises a monomer unit containing at least one fluorine atom. The polymer P2 is a polymer comprising a monomer unit containing at least one hydrophilic group. The polymers P1 and P2 may be in cross-linked or non-cross-linked form, and may be linear or branched.

[0019] According to a preferred embodiment, the composition comprising said polymers P1 and P2 and having a crystallization temperature as defined in the present invention enables a good compromise in the properties targeted according to the application for which the composition is used. Thus, when the composition is used for separators, it allows a good compromise between dry adhesion and solvent resistance, as demonstrated in this patent application.

[0020] Advantageously, the above-mentioned target properties are obtained when the crystallization temperature of the composition is Tc<-3.7496x+128, wherein x is the mass content of comonomer M1 based on the total weight of the polymer P1. Preferably, the crystallization temperature of the composition is Tc<-3.7496x+126, wherein x is the mass content of comonomer M1 based on the total weight of the polymer P1. More preferably, the crystallization temperature of the composition is Tc<-3.7496x+124, wherein x is the mass content of comonomer M1 based on the total weight of the polymer P1. In particular, the crystallization temperature of the composition is Tc<-3.7496x+122, wherein x is the mass content of comonomer M1 based on the total weight of the polymer P1. More particularly, the crystallization temperature of the composition is Tc<-3.7496x+120, wherein x is the mass content of comonomer M1 based on the total weight of the polymer P1. Preferably, the crystallization temperature of the composition is Tc<-3.7496x+118, wherein x is the mass content of comonomer M1 based on the total weight of the polymer P1. In an advantageous preferred manner, the crystallization temperature of the composition is Tc<-3.7496x+116, wherein x is the mass content of comonomer M1 based on the total weight of the polymer P1. In a preferentially preferred manner, the crystallization temperature of the composition is Tc<-3.7496x+115, wherein x is the mass content of comonomer M1 based on the total weight of the polymer P1.

[0021] Preferably, in the composition, the mass ratio between polymer P1 and polymer P2 ranges from 95 / 5 to 5 / 95, advantageously from 95 / 5 to 25 / 75, preferably from 95 / 5 to 40 / 60, more preferably from 95 / 5 to 50 / 50, in particular from 95 / 5 to 60 / 40, more preferably from 90 / 10 to 65 / 35.

[0022] Unless otherwise mentioned, the indicated contents are expressed on a weight basis. For all indicated ranges, the limits are included unless otherwise stated.

[0023] i) Polymer P1

[0024] Preferably, the polymer P1 is based on a vinylidene fluoride monomer (CF2═CH2 or VDF), ie it comprises monomer units derived from vinylidene fluoride. The polymer P1 may also be denoted by the abbreviation PVDF.

[0025] According to one embodiment, polymer P1 is a vinylidene fluoride homopolymer. In this case, x is equal to 0 and the crystallization temperature of the composition is less than 130°C.

[0026] According to another embodiment, polymer P1 is a copolymer of vinylidene fluoride and at least one comonomer M1 compatible with vinylidene fluoride. The comonomer M1 compatible with vinylidene fluoride can be halogenated (fluorinated, chlorinated or brominated) or non-halogenated. Examples of suitable fluorinated comonomers M1 are: vinyl fluoride, tetrafluoroethylene, hexafluoropropylene, trifluoroethylene, chlorotrifluoroethylene, trifluoropropylene and especially 3,3,3-trifluoropropylene, tetrafluoropropylene and especially 2,3,3,3-tetrafluoropropylene or 1,3,3,3-tetrafluoropropylene, hexafluoroisobutylene, perfluorobutylethylene, pentafluoropropylene and especially 1,1,3,3,3-pentafluoropropylene or 1,2,3,3,3-pentafluoropropylene, perfluoroalkyl vinyl ethers and especially those with the general formula Rf-O-CF=CF2, Rf is an alkyl group, preferably a C1-C4 alkyl group (preferred examples are perfluoropropyl vinyl ether and perfluoromethyl vinyl ether).

[0027] The fluorine-containing comonomer may include chlorine or bromine atoms. It may be particularly selected from bromotrifluoroethylene, chlorofluoroethylene, chlorotrifluoroethylene and chlorotrifluoropropylene. Chlorofluoroethylene may represent 1-chloro-1-fluoroethylene or 1-chloro-2-fluoroethylene. 1-chloro-1-fluoroethylene isomers are preferred. Chlorotrifluoropropylene is preferably 1-chloro-3,3,3-trifluoropropylene or 2-chloro-3,3,3-trifluoropropylene.

[0028] The VDF copolymers may also contain non-halogenated monomers, such as ethylene and / or acrylic or methacrylic comonomers.

[0029] The polymer P1 preferably comprises at least 50 mol % of vinylidene fluoride, advantageously at least 60 mol % of vinylidene fluoride, preferably at least 70 mol % of vinylidene fluoride. The comonomer M1 may be present in a content ranging from 1 wt % to 50 wt %, advantageously from 2 wt % to 30 wt %, relative to the weight of the polymer P1.

[0030] According to one embodiment, polymer P1 is a copolymer of vinylidene fluoride (VDF) and hexafluoropropylene (HFP) (P(VDF-HFP)), the weight percentage of hexafluoropropylene monomer units of which is from 2% to 30% by weight, advantageously from 2% to 25% by weight, preferably from 2% to 20% by weight, preferably from 4% to 15% by weight, relative to the weight of said polymer P1. According to another embodiment, polymer P1 is a copolymer of vinylidene fluoride (VDF) and hexafluoropropylene (HFP) (P(VDF-HFP)), the weight percentage of hexafluoropropylene monomer units of which is from 20% to 30% by weight, advantageously from 20% to 25% by weight, relative to the weight of said polymer P1.

[0031] According to one embodiment, polymer P1 is a copolymer of vinylidene fluoride and tetrafluoroethylene (TFE).

[0032] According to one embodiment, polymer P1 is a copolymer of vinylidene fluoride and chlorotrifluoroethylene (CTFE).

[0033] According to one embodiment, polymer P1 is a VDF-TFE-HFP terpolymer. According to one embodiment, polymer P1 is a VDF-TrFE-TFE terpolymer (TrFE is trifluoroethylene). In these terpolymers, the mass content of VDF is at least 10%, and the comonomers are present in variable proportions.

[0034] According to one embodiment, the polymer P1 comprises a monomer unit carrying at least one of the following functional groups: carboxylic acid, carboxylic anhydride, carboxylic ester, epoxy (e.g. glycidyl), amide, hydroxyl, carbonyl, mercapto, sulfide, oxazoline, phenol, ester, ether, siloxane, sulfonic acid, sulfuric acid, phosphoric acid, phosphonic acid groups. This functional group is introduced via a chemical reaction, which can be a copolymerization or grafting of a vinylidene fluoride (VDF) monomer with a monomer carrying at least one of said functional groups and a vinyl functional group copolymerizable with the VDF monomer, according to techniques well known to those skilled in the art, or by adsorbing a polymer carrying said functional group into the polymer P1. Thus, preferably, the monomer unit is derived from a polymer containing them and having a molar mass of less than 100 000 g / mol, preferably less than 50 000 g / mol, in particular less than 20 000 g / mol. The latter can be grafted onto or adsorbed by the polymer P1.

[0035] According to one embodiment, the functional group carries a carboxylic acid functional group, which is a (meth)acrylic acid type group selected from acrylic acid, methacrylic acid, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate and hydroxyethylhexyl (meth)acrylate. Thus, the polymer P1 may comprise monomer units derived from monomers selected from acrylic acid, methacrylic acid, methyl acrylate, methyl methacrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate and hydroxyethylhexyl methacrylate.

[0036] According to one embodiment, the unit carrying a carboxylic acid function also comprises heteroatoms chosen from oxygen, sulfur, nitrogen and phosphorus.

[0037] According to one embodiment, the functionality is introduced via a transfer agent used during the synthesis process. Preferably, the transfer agent is a polymer having a molar mass less than or equal to 20 000 g / mol and carrying functional groups selected from the group consisting of carboxylic acid, carboxylic anhydride, carboxylic ester, epoxy (e.g. glycidyl), amide, hydroxyl, carbonyl, mercapto, sulfide, oxazoline, phenols, esters, ethers, siloxanes, sulfonic acid, sulfuric acid, phosphoric acid, phosphonic acid groups; preferably carboxylic acid, carboxylic anhydride, carboxylic ester. Examples of transfer agents of this type are oligomers of acrylic acid. The transfer agent can be grafted onto polymer P1 or adsorbed by polymer P1.

[0038] The polymer P1 may comprise end groups consisting of the transfer agent. In particular, the transfer agent is a polymer having a molar mass less than or equal to 20 000 g / mol and carrying a functional group selected from a carboxylic acid or a carboxylic ester. The molar mass of the transfer agent can be determined by GPC analysis on a Waters 2695e device coupled to a Wyatt Wyatt NEON refractometer equipped with two PL gel mixed C columns and a guard column (7.8 mm ID×30 cm, 5 μm), under the following conditions: temperature: 35° C.; flow rate: 1.0 mL / min; injection volume: 100 μL; concentration in THF 1 mg / mL (HPLC grade); calibration using 12 poly(methyl methacrylate) samples ranging from 535 to 2 210 000 g / mol.

[0039] The functional group content of the polymer P1 is at least 0.01 mol %, preferably at least 0.1 mol %, and not more than 15 mol %, preferably not more than 10 mol %.

[0040] As used herein, the term "high molecular weight" is understood to mean a polymer P1 having a melt viscosity greater than 100 Pa.s, preferably greater than 500 Pa.s, more preferably greater than 1000 Pa.s at 232°C and 100 sec-1 according to the ASTM D-3835 method.

[0041] According to one embodiment, the polymer P1 carrying functional groups can be crosslinked by self-condensation of its functional groups or by reaction with catalysts and / or crosslinking agents, such as melamine resins, epoxy resins, etc., and also known low molecular weight crosslinkers, such as di- or higher polyisocyanates, polyaziridines, polycarbodiimides, polyoxazolines, dialdehydes such as glyoxal, acetoacetates, malonates, acetals, thiols and acrylates (which are di- and trifunctional), cycloaliphatic epoxy molecules, organosilanes such as epoxysilanes and aminosilanes, carbamates, diamines and triamines, inorganic chelating agents such as certain zinc and zirconium salts, titanium, glycourils and other aminoplasts. In some cases, functional groups originating from other polymeric components such as surfactants, initiators or seed particles can participate in the crosslinking reaction. When two or more functional groups are involved in the crosslinking process, complementary reactive group pairs are, for example, hydroxyl-isocyanate, acid-epoxy, amine-epoxy, hydroxyl-melamine, acetoacetate-acid. Acrylate and / or methacrylate monomers that do not contain functional groups that can enter into a crosslinking reaction after polymerization should preferably account for 70% or more of the total weight of the monomer mixture, more preferably should be greater than 90%. According to one embodiment, polymer P1 comprises a crosslinking agent selected from isocyanates, diamines, adipic acid, dihydrazides and combinations thereof.

[0042] According to certain embodiments, PVDF homopolymer and VDF copolymer are made of bio-based VDF. The term "bio-based" means "derived from biomass". This makes it possible to improve the ecological footprint of the separator. Bio-based VDF can be characterized by a content of renewable carbon (i.e., carbon from a natural source of biomaterial or biomass) of at least 1 at%, as determined by the content of 14C according to standard NF EN 16640. The term "renewable carbon" means that the carbon is of natural origin and is derived from biomaterial (or from biomass), as shown below. According to certain embodiments, the biocarbon content of VDF can be greater than 5%, preferably greater than 10%, preferably greater than 25%, preferably greater than or equal to 33%, preferably greater than 50%, preferably greater than or equal to 66%, preferably greater than 75%, preferably greater than 90%, preferably greater than 95%, preferably greater than 98%, preferably greater than 99%, advantageously equal to 100%.

[0043] The P1 homopolymer and the VDF copolymer used in the present invention can be obtained via known polymerization methods such as emulsion polymerization or suspension polymerization.

[0044] According to one embodiment, they are prepared by an emulsion polymerization process in the absence of fluorosurfactants.

[0045] The polymerization of vinylidene fluoride preferably produces a latex having a solid content of from 10% to 60%, preferably from 10% to 50%, by weight, and having a weight average particle size of less than 1 micron, preferably less than 1000nm, preferably less than 800nm ​​and more preferably less than 600nm. The weight average size of the particles is generally at least 20nm, preferably at least 50nm, and advantageously the average size is in the range of 100-400nm. The polymer particles may form agglomerates having a weight average size of from 1 to 30 microns, preferably from 2 to 20 microns. During formulation and application to the substrate, the agglomerates may be broken into discrete particles.

[0046] ii) Polymer P2

[0047] As mentioned above, the polymer P2 comprises a polymer derived from the formula R 1 R 2 C=C(R 3 )C(O)R monomer M2 monomer unit, wherein the substituent R 1 , R 2 and R 3 independently selected from H and C1-C5 alkyl; R is selected from -NH C(CH3)2CH2C(O)CH3 or -OR', wherein R' is selected from H and C1-C5 alkyl optionally substituted by one or more -OH groups or a 5- or 10-membered heterocyclic ring containing at least one nitrogen atom in its ring chain 18 The heterocyclic ring may be saturated or unsaturated or aromatic. The heterocyclic ring may be monocyclic or bicyclic. The heterocyclic ring may be a pyrrole, pyrrolidine, pyridine, piperidine, pyrimidine, pyrazine, 1,4-dihydropyridine, indole, oxindole, isatin, quinoline, isoquinoline, quinazoline, imidazoline, pyrazolidine, 2-pyrrolidone, delta-lactam, succinimide, 2-imidazolidinone or 4-imidazolidinone ring. The heterocyclic ring may be substituted with one or more C1-C5 alkyl groups. As described above, C1-C 18 The alkyl group is optionally substituted by the heterocycle. The latter may be bound to the alkyl chain via a nitrogen atom or any other atom forming a heterocycle. Preferably, the heterocycle is 2-pyrrolidone, delta-lactam, succinimide, 2-imidazolidinone or 4-imidazolidinone.

[0048] Preferably, the polymer P2 comprises a 1 R 2 C=C(R 3 )C(O)R (meth) acrylate monomer M2 monomer unit, wherein the substituent R 1 , R 2 and R 3R is selected from -NHC(CH3)2CH2C(O)CH3 or -OR', wherein R' is selected from C1-C5 alkyl optionally substituted by one or more -OH groups or a 5- or 10-membered heterocyclic ring containing at least one nitrogen atom in its ring chain; 18 The polymer P2 comprises an alkyl group derived from the formula R 1 R 2 C=C(R 3 )C(O)R, wherein the substituents R1, R2 and R3 are independently selected from H and C1-C5 alkyl; R is -OR', wherein R' is selected from H and C1-C5 alkyl optionally substituted with one or more -OH groups. 18 Preferably, the heterocycle is as defined above, in particular, the heterocycle is 2-pyrrolidone, delta-lactam, succinimide, 2-imidazolidinone or 4-imidazolidinone. The term "alkyl (meth)acrylate" encompasses alkyl acrylates and alkyl methacrylates.

[0049] According to a preferred embodiment, the substituent R' is selected from H, methyl, ethyl, propyl, n-butyl, isobutyl, tert-butyl, n-dodecyl, pentyl, isopentyl, hexyl, 2-ethylhexyl, lauryl, n-octyl, hydroxybutyl, hydroxypropyl, hydroxyethyl, and ethyl, which is substituted by: urea, hydroxyethyl, hydroxypropyl or hydroxybutyl.

[0050] In particular, the polymer P2 comprises a polymer derived from the formula R 1 R 2 C=C(R 3 )C(O)R (meth) acrylate monomer M2 monomer unit, wherein the substituent R 1 and R 2 H; R 3 is H or CH3; R is -OR', wherein R' is selected from H, methyl, ethyl, propyl, n-butyl, isobutyl, tert-butyl, hydroxyethyl, hydroxypropyl, hydroxybutyl, 2-pyrrolidone, δ-lactam, succinimide, 2-imidazolidinone and 4-imidazolidinone.

[0051] Therefore, (meth) alkyl acrylate can be methyl acrylate, ethyl acrylate, propyl acrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, n-dodecyl acrylate, amyl acrylate, isopentyl acrylate, hexyl acrylate, 2-ethylhexyl acrylate, diacetone acrylamide, lauryl acrylate, n-octyl acrylate, hydroxypropyl methacrylate, hydroxybutyl acrylate, hydroxyethyl methacrylate, hydroxyethyl acrylate, acrylic acid, methacrylic acid, methyl acrylate, methyl methacrylate, urea-methacrylate and mixtures thereof. Wherein, preferably alkyl contains alkyl acrylate of 1-8 carbon atom, more preferably alkyl contains alkyl acrylate of 1-5 carbon atom. These compounds can be used alone or as two or more mixtures use. Therefore, described polymer P2 can be the homopolymer of monomer M2 as defined above or the copolymer derived from the mixture of one or more monomers M2 as defined above.

[0052] The term "acrylate" herein includes both acrylate and methacrylate.

[0053] Optional ethylenically unsaturated compounds copolymerizable with the alkyl acrylates and alkyl methacrylates include:

[0054] - (A) an alkenyl compound containing a functional group, and

[0055] - (B) an alkenyl compound having no functional group.

[0056] The alkenyl compound (A) containing a functional group includes, for example, α, β-unsaturated carboxylic acids such as acrylic acid, methacrylic acid, fumaric acid, crotonic acid, itaconic acid, etc.; vinyl ester compounds such as vinyl acetate, vinyl neodecanoate, etc.; amide compounds such as acrylamide, methacrylamide, N-methylacrylamide, N-methylmethacrylamide, N-hydroxymethylacrylamide, N-hydroxymethylmethacrylamide, N-alkylacrylamide, N-alkylmethacrylamide, N,N-dialkylacrylamide, N,N-dialkylmeth ... Acrylic acid esters such as 2-hydroxyethyl acrylate, N-dialkylaminoethyl acrylate, glycidyl acrylate, n-dodecyl acrylate, fluoroalkyl acrylate, etc.; and methacrylates such as dialkylaminoethyl methacrylate, fluoroalkyl methacrylate, 2-hydroxyethyl methacrylate, n-octyl methacrylate, tert-butyl methacrylate, glycidyl methacrylate, ethylene glycol dimethacrylate, etc.; maleic anhydride, and alkenyl glycidyl ether compounds such as allyl glycidyl ether, etc. Among them, acrylic acid, methacrylic acid, itaconic acid, fumaric acid, N-hydroxymethyl acrylamide, N-hydroxymethyl methacrylamide, diacetone acrylamide, 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, and allyl glycidyl ether are preferred. These compounds can be used alone or as a mixture of two or more.

[0057] The alkenyl compound (B) not containing a functional group includes, for example, conjugated dienes such as 1,3-butadiene, isoprene, etc.; divinyl hydrocarbon compounds such as divinylbenzene, etc.; and alkenyl cyanides such as acrylonitrile, methacrylonitrile, etc. Among them, preferred compounds are 1,3-butadiene and acrylonitrile. These compounds can be used alone or as a mixture of two or more.

[0058] Preferably, the functional alkenyl compound (A) is used in a proportion of less than 50% by weight relative to the weight of the monomer mixture, and the non-functional alkenyl compound (B) is used in a proportion of less than 30% by weight relative to the weight of the monomer mixture.

[0059] Method for preparing the composition

[0060] The composition according to the present invention can be prepared by a method comprising the following steps:

[0061] a) providing a reactor containing said polymer P1, said polymer P1 comprising monomer units derived from vinylidene fluoride,

[0062] b) the formula R as defined in the present patent application 1 R 2 C=C(R 3)C(O)R, adding at least one monomer M2 to the reactor and contacting the polymer P1 with the at least one monomer M2 for at least 5 minutes;

[0063] c) carrying out polymerization of the at least one monomer M2 to form the composition.

[0064] The polymer P1 is preferably in the form of a latex.

[0065] During step b), a compound of formula R as defined in the present patent application is added 1 R 2 C=C(R 3 )C(O)R is added to the reactor. During step b), preferably all monomers constituting the polymer P2 are added, if they contain different monomers of formula R 1 R 2 C=C(R 3 )C(O)R. The addition of all of the at least one monomer M2 constituting the polymer P2 in step b) allows to improve the mixing tightness between the polymer P1 and all of the monomer units constituting the polymer P2. Preferably, the at least one monomer M2 is selected from methyl acrylate, ethyl acrylate, propyl acrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, n-dodecyl acrylate, amyl acrylate, isoamyl acrylate, hexyl acrylate, 2-ethylhexyl acrylate, diacetone acrylamide, lauryl acrylate, n-octyl acrylate, hydroxybutyl acrylate, hydroxypropyl methacrylate, hydroxyethyl methacrylate, hydroxyethyl acrylate, acrylic acid, methacrylic acid, methacrylic acid, methyl methacrylate, ureido methacrylate and combinations thereof. Step b) may also optionally include the addition of alkenyl compounds (A) and / or (B) as described above for polymer P2.

[0066] During step b), polymer P1 and at least one monomer M2 are contacted for a time long enough for said monomer M2 to impregnate the particles of polymer P1 and then polymerize. This contact time is at least 5 minutes, preferably 10 minutes, in particular at least 15 minutes, more particularly at least 20 minutes. Preferably, monomer M2 is added before the initiator. This allows to obtain the preferred compositions of the invention.

[0067] The method further comprises a step c) during which the at least one monomer M2 is polymerized. Step c) is preferably carried out in the presence of water. Step c) of the polymerization of the at least one monomer M2 is carried out in the presence of an initiator. The initiator may be an initiator of the persulfate type, such as sodium persulfate, potassium persulfate, barium persulfate or ammonium persulfate; an alkali metal hydrogen sulfite; a peroxide, such as benzoyl peroxide or dicumyl peroxide; a hydroperoxide, such as methyl hydroperoxide or tert-butyl hydroperoxide; an acyloin such as benzoin; a peracetate, such as methyl peracetate or tert-butyl peracetate; a perbenzoate, such as tert-butyl perbenzoate; a peroxalate, such as dimethyl peroxalate or di(tert-butyl) peroxalate; an azo compound, such as azobisisobutyronitrile or dimethyl azobisisobutyrate. The initiator is preferably added in an amount of 0.005% to 1% by weight, based on the weight of the at least one monomer M2 and the optional alkenyl compounds (A) and (B) (if present).

[0068] Optionally, step c) is carried out in the presence of a chain transfer agent. The chain transfer agent may be an oxygen-containing compound, such as an alcohol, carbonate, ketone, ester or ether; a halocarbon or hydrohalocarbon compound, such as a chlorocarbon, a hydrochlorocarbon, a chlorofluorocarbon or a hydrochlorofluorocarbon; ethane or propane. Alternatively, the chain transfer agent may be a polymer having a molar mass less than or equal to 20 000 g / mol and carrying functional groups selected from the following groups: carboxylic acid, carboxylic anhydride, carboxylic ester, epoxy (such as glycidyl), amide, hydroxyl, carbonyl, mercapto, sulfide, oxazoline, phenol, ester, ether, siloxane, sulfonic acid, sulfuric acid, phosphoric acid and phosphonic acid groups. Examples of transfer agents of this type are oligomers of acrylic acid. Preferably, if it is present, the chain transfer agent is added in a content of 0.05 to 5% by weight, based on the weight of the at least one monomer M2 and optionally the alkenyl compounds (A) and (B) (if present).

[0069] As mentioned in the scheme described in WO 2007 / 018783, other compounds may also be present in the practice of the composition according to the present method.

[0070] Step c) may be performed at a temperature of 20° C. to 160° C. Step c) may be performed at a pressure of 280 to 20 000 kPa.

[0071] Preferably, steps b) and c) are carried out under stirring.

[0072] The composition is preferably obtained in the form of a latex, ie in the form of a dispersion in an aqueous medium.

[0073] Thus, the composition is an aqueous dispersion obtained by emulsion polymerization of 5 to 100, preferably 5 to 95 parts by weight of a monomer mixture in an aqueous medium in the presence of 100 parts by weight of particles of a polymer P1 as defined above, the monomer mixture comprising at least one monomer M2 selected from alkyl acrylates whose alkyl groups contain 1 to 18 carbon atoms and alkyl methacrylates whose alkyl groups contain 1 to 18 carbon atoms, and optionally an ethylenically unsaturated compound copolymerizable with alkyl acrylates and alkyl methacrylates. The particles of polymer P1 are used as seeds for the polymerization of monomer M2. The particles of polymer P1 can be added to the polymerization system in any state, as long as they are dispersed in the aqueous medium in the form of particles. Since polymer P1 is usually prepared in the form of an aqueous dispersion, it is convenient to use the prepared aqueous dispersion as seed particles.

[0074] The product of the polymerization is a latex, which can be used in this form, usually after filtering out the solid by-products of the polymerization process. In order to be used in the form of a latex, the latex can be stabilized by adding a surfactant, which can be the same or different (where appropriate) from the surfactant present during the polymerization. Such surfactants added in addition can be, for example, ionic or non-ionic surfactants. In terms of composition (e.g., HFP comonomer content) and / or molecular mass, particles of polymer P1 used as seeds can have uniform or non-uniform features or gradients between the core and the surface of the particles. In the composition, the P1 and P2 polymer chains are entangled to form an interpenetrating polymer network (IPN) defined by IUPAC; it is different from a mixture of preformed polymers. Preferably, the P1 and P2 polymer chains are entangled to form a sequential interpenetrating polymer network defined by IUPAC.

[0075] Partition

[0076] The composition according to the present invention can be used as one of the materials for preparing a separator in an electrochemical device. In this application, the mass ratio P1 / P2 preferably ranges from 95 / 5 to 5 / 95, particularly from 95 / 5 to 40 / 60, more preferably from 90 / 10 to 50 / 50. Preferably, polymer P1 is a copolymer of vinylidene fluoride and at least one comonomer compatible therewith as described above. In particular, polymer P1 can be a copolymer (P(VDF-HFP)) of vinylidene fluoride (VDF) and hexafluoropropylene (HFP), wherein the weight percentage of the hexafluoropropylene monomer unit is 2% to 30% by weight, advantageously 2% to 25% by weight, preferably 2% to 20% by weight, relative to the weight of polymer P1; or a copolymer of vinylidene fluoride and tetrafluoroethylene (TFE); or a copolymer of vinylidene fluoride and chlorotrifluoroethylene (CTFE); or a VDF-TFE-HFP terpolymer, as described above. Furthermore, the polymer P1 may comprise monomer units selected from acrylic acid, methacrylic acid, methyl acrylate, methyl methacrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate and hydroxyethylhexyl methacrylate.

[0077] The composition is preferably used in a separator coating. In addition to the composition, the separator coating may contain inorganic particles, which are used to form micropores (gaps between inorganic particles) in the coating. The addition of inorganic particles can also contribute to heat resistance or improve wettability. According to one embodiment, the coating includes from 50% to 99% by weight of inorganic particles relative to the weight of the coating. These inorganic particles must be electrochemically stable (not subject to oxidation and / or reduction within the voltage range used). In addition, the powdered inorganic material preferably has high ionic conductivity. Low-density materials are better than higher-density materials because the weight of the produced battery can be reduced. The dielectric constant is preferably equal to or greater than 5. According to one embodiment, the inorganic particles are selected from: BaTiO3, Pb(Zr,Ti)O3, Pb 1-x La x Zr y O3(0 <x<1,0<y<1)、PbMg3Nb 2 / 3)3, PbTiO3, hafnium oxide (HfO (HfO2)), SrTiO3, SnO2, CeO2, MgO, NiO, CaO, ZnO, Y2O3, boehmite (γ-AlO (OH)), Al2O3, TiO2, SiC, ZrO2, borosilicate, BaSO4, nanoclay or a mixture thereof. In this case, the ratio of solids of polymers P1 and P2 to inorganic particles is 0.5 to 40 parts by weight of solids of polymers P1 and P2 per 60 to 99.5 parts by weight of inorganic particles. Advantageously, the ratio of solids of polymers P1 and P2 to inorganic particles is 0.5 to 35 per 65 to 99.5 parts by weight of inorganic particles. Preferably, the ratio of solids of polymers P1 and P2 to inorganic particles is 0.5 to 30 per 70 to 99.5 parts by weight of inorganic particles. The separator coating may optionally contain 0 to 15 wt %, preferably 0.1 to 10 wt %, of additives based on the polymer, selected from thickeners, pH regulators, anti-settling agents, surfactants, wetting agents, fillers, defoamers, and fugitive or non-fugitive adhesion promoters. The fillers mentioned in the additives are different from the above-mentioned inorganic particles.

[0078] The separator according to the present invention includes a coating as described above, which is optionally arranged on one or two faces of a porous support. In this case, the coating is used to coat the support of the separator in the form of a single layer or multiple layers on at least one face. There is no particular restriction on the selection of the support coated with the coating of the present invention, as long as it is a porous substrate with holes. The support may include a single layer or multiple different layers. When it contains multiple layers, the coating as described in the present invention is arranged on the outer surface of the support, that is, arranged on the face that will first contact the electrolyte composition used in the battery. Advantageously, the coating is applied to the support by an aqueous approach or by a solvent approach. The porous substrate can be in the form of a membrane or a fiber fabric. When the porous substrate is a fiber, it can be a non-woven web forming a porous web, such as a web obtained by direct spinning or meltblowing (spunbond or meltblown) or electrospinning. Examples of porous substrates that can be used as carriers in the present invention include, but are not limited to, polyolefins, polyethylene terephthalate, polybutylene terephthalate, polyesters, polyacetals, polyamides, polycarbonates, polyimides, polyetheretherketones, polyethersulfones, polyphenylene oxides, polyphenylene sulfides, polyethylene naphthalate, or mixtures thereof. However, other heat-resistant engineering plastics can be used without particular restrictions. Nonwoven materials made of natural or synthetic materials can also be used as substrates for separators. Porous substrates typically have a thickness of 1 μm to 50 μm, and are typically membranes or cast nonwovens obtained by extrusion and stretching (wet or dry). The porous substrate preferably has a porosity of 5% to 95%. The average size (diameter) of the pores is preferably 0.001 to 50 μm, more preferably 0.01 to 10 μm.

[0079] According to an alternative embodiment, the separator does not comprise a porous support. In this case, the separator consists of a coating as described above and comprising the composition; it is deposited directly on the cathode or on the anode of the electrochemical device. The absence of a porous support allows limiting the production costs of the electrochemical device and its size. In this case, the coating replaces the porous support. In this embodiment, the polymer resin preferably has a porosity of 5% to 95%. The average size of the pores of the polymer resin is preferably between 0.001 and 50 μm, more preferably between 0.01 and 10 μm.

[0080] According to another alternative embodiment, the separator does not include a porous support and the separator is in gel form. The separator is as described in the present patent application. The separator is formed into gel form by conventional techniques such as solvent casting or extrusion. The separator coating of the present invention has an excellent compromise of properties for separator coating applications: good dry adhesion and wet adhesion, good electrolyte solvent tolerance, characterized by good storage integrity and moderate swelling.

[0081] Example

[0082] The crystallization temperature was measured by DSC during cooling according to the following procedure:

[0083] -Heating from 10°C to 200°C at 10°C / min

[0084] -Keep at 200℃ for 1min

[0085] - Cool from 200°C to -80°C at 5°C / min.

[0086] Preparation of the composition according to the invention (Example 1)

[0087] The polymer P1 used in Example 1 is a latex of a P(VDF-HFP) copolymer. It is used as a seed to synthesize the composition according to the present patent application via an emulsion polymerization method according to the scheme described in WO 2007 / 018783 in the presence of a chain transfer agent of the acrylic oligomer type with a molar mass of less than 20 000 g / mol. In Example 1, the monomer M2 used to prepare the polymer P2 is a mixture of methyl (meth)acrylate, ethyl acrylate and methacrylic acid in a mass ratio of 58 / 40 / 2. The monomer M2 is contacted with the polymer P1 for 25 minutes, and then the polymerization of the monomer M2 is carried out.

[0088] Preparation of latex mixture (Example 2 - comparative composition): Polymer P1 and polymer P2 were prepared independently of each other by an emulsion polymerization process. In this example, polymer P2 was prepared in the absence of seeds of polymer P1. The two polymers in latex form were then mixed in a ratio of 70 / 30. The composition of polymers P1 and P2 was identical to that of polymers P1 and P2 of Example 1.

[0089] Comparative composition of Example 3

[0090] Example 3 was carried out using a composition consisting of polymer P1 from Example 1 in latex form.

[0091] Preparation of coating composition:

[0092] At room temperature: 10 g of alumina (Sumitomo Chemical AES-11) was added to 20 g of a 0.5 wt% CMC aqueous solution (Nippon paper FT-3) and then dispersed in a mixer (Filmix Model 40-L) at 30 m / s for 30 seconds. To this dispersion was added a latex (or in the case of a mixture of PVDF latex and acrylic latex, both latexes were added according to the proportions indicated in the table) in order to incorporate 4 g of the corresponding polymer or polymers (the amount of latex was adjusted according to the solid proportion of each latex in the range of 30%-45%) and softened water to complete a total of 50 g of the formulation. The mixture was then homogenized at 600 rpm for 10 minutes with a vertical stirrer (IKA, Euro-ST). 0.24 g of a wetting agent (BYK349) was added to 48 g of this mixture in order to promote the spreading of the formulation on the separator and mixed under the same conditions as the latex.

[0093] Application of coating composition:

[0094] The coating composition was applied to a Celgard 2400 separator sample (single layer PP, thickness 25 μm, width 89 mm, length about 30 cm) using a manual coater (bar coater Hohsen Corp., wet deposit thickness of 23 μm, manual coating speed of about 100 mm / sec) at room temperature to 22° C., and then dried on the board at 65° C. for 10 min. The dried deposit had a measured thickness of 5-6 μm, depending on the sample (micrometer Mitsutoyo Digimatic Indicator IDH053D). The separator obtained had a width of 89 mm and a length of 30 cm.

[0095] The results are shown in Table 1 below.

[0096] [Table 1]

[0097]

[0098] The separator coating according to the invention has an excellent compromise of properties for the target application: good dry adhesion, good electrolyte solvent resistance, characterized by good storage integrity. On the other hand, the comparative examples (where the crystallization temperature is above the value defined by the equation -3.7496x+130) show at least one very unfavorable property.

Claims

1. A composition comprising a polymer P1 comprising monomer units derived from vinylidene fluoride and optionally derived from a comonomer M1 compatible with vinylidene fluoride, and a polymer P2 comprising a monomer unit derived from a monomer of formula R 1 R 2 C=C(R 3 )C(O)R monomer M2 monomer unit, wherein the substituent R 1 , R 2 and R 3 R is selected from -NHC(CH3)2CH2C(O)CH3 or -OR', wherein R' is selected from H and C1-C5 alkyl, which is optionally substituted by one or more -OH groups or a five-membered or six-membered heterocyclic ring containing at least one nitrogen atom in its ring chain; 18 Alkyl, characterized in that The crystallization temperature of the composition is Tc<-3.7496x+130, wherein x is the mass content of the comonomer M1 based on the total weight of the polymer P1.

2. The composition according to claim 1, characterized in that The mass ratio P1 / P2 ranges from 95 / 5 to 5 / 95, advantageously from 95 / 5 to 25 / 75, preferably from 95 / 5 to 40 / 60, in particular from 95 / 5 to 50 / 50.

3. A composition according to any one of the preceding claims, characterised in that The polymer P1 is chosen from homopolymers of vinylidene fluoride and copolymers based on vinylidene fluoride and at least one comonomer M1 that is compatible with vinylidene fluoride.

4. Composition according to the preceding claim, characterized in that The at least one comonomer M1 compatible with vinylidene fluoride is selected from the group consisting of vinyl fluoride, tetrafluoroethylene, hexafluoropropylene, trifluoroethylene, chlorotrifluoroethylene, trifluoropropylene, tetrafluoropropylene, hexafluoroisobutylene, perfluorobutylethylene, pentafluoropropylene, perfluoroalkyl vinyl ether, bromotrifluoroethylene, chlorofluoroethylene, chlorotrifluoroethylene, chlorotrifluoropropylene and ethylene or mixtures thereof.

5. A composition according to any one of the preceding claims, characterised in that The polymer P1 comprises: at least one monomer unit with the following functional groups, wherein the functional groups are selected from carboxylic acid, carboxylic anhydride, carboxylic ester, epoxy, amide, hydroxyl, carbonyl, mercapto, sulfide, oxazoline, phenol, ester, ether, siloxane, sulfonic acid, sulfuric acid, phosphoric acid or phosphonic acid groups; preferably at least one monomer unit with the following functional groups, wherein the functional groups are selected from carboxylic acid, carboxylic anhydride, carboxylic ester, hydroxyl, carbonyl and mercapto.

6. A composition according to any one of the preceding claims, characterised in that The polymer P2 contains monomer units derived from a monomer M2 selected from the group consisting of methyl acrylate, ethyl acrylate, propyl acrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, n-dodecyl acrylate, amyl acrylate, isoamyl acrylate, hexyl acrylate, 2-ethylhexyl acrylate, diacetone acrylamide, lauryl acrylate, n-octyl acrylate, hydroxypropyl methacrylate, hydroxybutyl acrylate, hydroxyethyl methacrylate, hydroxyethyl acrylate, acrylic acid, methacrylic acid, methacrylic acid, methyl methacrylate, ethyl methacrylate, propyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, n-dodecyl methacrylate, amyl methacrylate, isoamyl methacrylate, hexyl methacrylate, 2-ethylhexyl methacrylate, lauryl methacrylate, n-octyl methacrylate, ureido methacrylate and mixtures thereof.

7. A composition according to any one of the preceding claims, characterised in that The crystallization temperature of the composition is Tc<-3.7496x+128, wherein x is the mass content of the comonomer M1 based on the total weight of the polymer P1.

8. A composition according to any one of the preceding claims, characterised in that The composition is in the form of a latex.

9. A separator for an electrochemical device selected from the group consisting of Li-ion, capacitors, double-layer capacitors, and fuel cell membrane electrode assemblies (MEAs), the separator comprising a porous support and the composition according to any one of the preceding claims 1 to 8.

10. A separator according to the preceding claim, characterised in that The composition has a mass ratio P1 / P2 in the range of 95 / 5 to 5 / 95. 11 . A Li-ion secondary battery comprising an anode, a cathode and a separator, wherein the separator is the separator according to claim 9 or claim 10.

Citation Information

Patent Citations

  • Binder composition, separator including binder formed from the binder composition, lithium battery including the separator, and method of preparing the binder composition

    US20150155539A1

  • Polymerization of fluoropolymers using non-fluorinated surfactants

    WO2007018783A2